2021
DOI: 10.3390/ijms222313130
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Silicon Nitride Surface Chemistry for Facilitating Odontogenic Differentiation of Rat Dental Pulp Cells

Abstract: Silicon nitride (Si3N4) can facilitate bone formation; hence, it is used as a biomaterial in orthopedics. Nevertheless, its usability for dentistry is unexplored. The aim of the present study was to investigate the effect of Si3N4 granules for the proliferation and odontogenic differentiation of rat dental pulp cells (rDPCs). Four different types of Si3N4 granules were prepared, which underwent different treatments to form pristine as-synthesized Si3N4, chemically treated Si3N4, thermally treated Si3N4, and Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, these results align with previous studies highlighting the superior properties of silicon nitride in stimulating osteoblast differentiation and promoting new bone formation. 11 , 45 47 48 For example, Lee et al 45 developed a silicon nitride reinforced gelatin/chitosan cryogel system (SiN-GC) by incorporating silicon nitride microparticles into a gelatin/chitosan cryogel (GC). Their findings confirmed enhanced cell proliferation, mineralization, and upregulation of osteogenic genes in MC3T3-E1 preosteoblast cells cultured on SiN-GC scaffolds compared to GC scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these results align with previous studies highlighting the superior properties of silicon nitride in stimulating osteoblast differentiation and promoting new bone formation. 11 , 45 47 48 For example, Lee et al 45 developed a silicon nitride reinforced gelatin/chitosan cryogel system (SiN-GC) by incorporating silicon nitride microparticles into a gelatin/chitosan cryogel (GC). Their findings confirmed enhanced cell proliferation, mineralization, and upregulation of osteogenic genes in MC3T3-E1 preosteoblast cells cultured on SiN-GC scaffolds compared to GC scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Si3N4, there is currently a limited number of studies applied to the dental area, despite the fact that there are studies of its biological response since 1989 [37]. Some interesting characteristics of this material is that it shows resistance to bacteria and to biofilm formation in in vivo studies [38,39].…”
Section: Biofilm Formationmentioning
confidence: 99%
“…On the other hand, in the case of humans, applications have been made mainly focused on surgical procedures such as: spine surgery [167], orthopedics [168], maxillofacial [169] among others [170]. Finally, Si3N4 there are very few publications in in vivo studies, but despite this there are some works reported in animals [37,83,171]. Finally, in the case of human studies, spinal and lumbar prosthetic applications have been made [172,173].…”
Section: In Vivo Studiesmentioning
confidence: 99%